Cytotoxic Activity of Metal Complexes of Biogenic Polyamines: Polynuclear Platinum(II) Chelates - Teixeira, Luísa J. (2004)
Several polynuclear Pt(II) chelates with biogenic polyamines were synthesized and screened for their potential antiproliferative and cytotoxic activity in different human cancer cell lines. To gather information regarding the structure−activity relationships underlying their biological activity, the complexes studied were designed to differ in geometrical parameters such as the nature of the ligand and the number and chemical environment of the metal centers. Distinct effects were found for different cell lines and different structural characteristics of the complexes; chelates II, III, and IV displayed specificity toward the HeLa and HSC-3 epithelial-type cells, while V, VI, and VII were clearly more effective against the THP-1, MOLT-3, and CCRF-CEM leukemia cell lines. The toxicity of these Pt(II) complexes on noncancer cells was, in all cases, found to be reversed upon drug removal.